Quality of life after traumatic loss and the role of social support - examining the psychological consequences of war twenty-five years later - Radetić Lovrić, Sanja; Pecanac, Aleksandra (Psihološka istraživanja, 2020)
The research was conducted with the aim of understanding the far-reaching psychological consequences of the war that took place in the territory of former Yugoslavia (1991-1995). The study examines the relationships between experienced war stressors and wartime traumatic experience of loss, quality of life and mental health, and the role of social support between three categories of respondents: the first consists of respondents who lost a close family member in the war and whose remains have not been found to date; the second category consists of persons who lost a close family member in the war; while the third category consists of respondents who participated in the war socialization but did not experience the loss of a close family member in the war. The survey used the daily stressors, war stressors, and psychosomatic symptoms lists, the Depression Symptoms Questionnaire, the Subjective Happiness Scale, the Life Satisfaction Scale, and the Social Support Significance Assessment Scale. The results show that respondents who continue to search for the body of a missing family member have a lower quality of life than the other two categories of respondents, have experienced a greater number of war stressors, are more susceptible to daily stress, and have a more pronounced presence of depressive and psychosomatic symptoms. The role of social support in the trauma recovery process remains unclear. The results of the study were discussed in relation to  completed and prolonged traumatic loss.
Keywords: traumatic loss, stressors, quality of life, social support, missing persons